A Panel Discussion on Human Factors Considerations for Persons Aging-in-Place with Disability. (November 2019) - Beer, Jenay M.; Rogers, Wendy A.; Sanford, Jon A.; Remillard, Elena T.; Phillips, Carolyn; Campbell, Margaret
Persons with disability are living longer and are at risk of experiencing greater disability as a result of additional age-related declines. These individuals, "aging with disability", could benefit greatly from technology supports – if such supports are designed and developed with their capabilities and limitations in mind. To ensure technology interventions meet user requirements, it is important to identify and implement human factors considerations. This panel brings together leaders at the intersection of aging and disability research, who are members of TechSAge (Rehabilitation and Engineering Research Center on Technologies to Support Aging-in-Place for People with Long-Term Disabilities) – a multi-site, multi-disciplinary research collaboration aiming to understand the complex interaction between age-related changes and disability when designing and developing technology interventions. Specifically, the panel will address four overarching themes, integral to the success of TechSAge: (1) understanding user needs; (2) innovative environmental supports; (3) translational technology interventions; and (4) closing the gap between research and practice. This discussion will highlight the substantial research in the fields of aging and disability, yet emphasize the importance of bridging the gap between these two fields. Human factors, in particular, has potential to contribute much to this area of study, with the potential to improve the lives of older adults with disability wishing to remain longer in their homes of choice.